ถ่านกัมมันต์จากวัสดุเหลือใช้ทางการเกษตรโดยการกระตุ้นทางเคมีเพื่อการประยุกต์ใช้กำจัดสารมลพิษในน้ำ - Phothitontimongkol, Theeradit (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2017)
Activated Carbon from Agricultural Residues by Chemical Activation for the Application of Pollutant Removal in Water Theeradit Phothitontimongkol รับบทความ: 21 เมษายน 2559; ยอมรับตีพิมพ์: 9 พฤษภาคม 2560 บทคัดย่อ บทความฉบับนี้มีวัตถุประสงค์เพื่อทบทวน สรุปประเด็น และเผยแพร่ความรู้เกี่ยวกับการเตรียมถ่านกัมมันต์จากวัสดุเหลือใช้ทางการเกษตรด้วยวิธีการกระตุ้นทางเคมีเพื่อใช้กำจัดสารมลพิษในน้ำ ถ่านกัมมันต์เป็นวัสดุที่มีลักษณะโครงสร้างที่มีพื้นที่ผิวและปริมาตรรูพรุนสูงประมาณ 600 – 2,400 ตารางเมตรต่อกรัม และ 0.20 – 1.00 ลูกบาศก์เซนติเมตรต่อกรัม ตามลำดับ โดยมีธาตุคาร์บอนเป็นองค์ประกอบหลักประมาณร้อยละ 80 – 90 ซึ่งได้จากวัสดุเหลือใช้ทางการเกษตร เช่น ฟางข้าว ซังข้าวโพด กะลามะพร้าว ขุยมะพร้าว เปลือกปาล์ม ไม้เนื้อแข็ง ขั้นตอนในการเตรียมถ่านกัมมันต์มี 2 ขั้นตอน คือ การคาร์บอไนซ์ และการกระตุ้น ในขั้นตอนการกระตุ้นมี 2 วิธี ได้แก่ การกระตุ้นทางกายภาพและการกระตุ้นทางเคมี เมื่อเปรียบเทียบการกระตุ้นทางกายภาพและทางเคมี พบว่า การกระตุ้นทางเคมีมีการศึกษาและนำไปใช้งานมากกว่าการกระตุ้นทางกายภาพ เนื่องจากใช้อุณหภูมิต่ำและระยะเวลาน้อยในการกระตุ้น แต่ได้ถ่านกัมมันต์ที่พื้นที่ผิวและปริมาตรรูพรุนสูง สารเคมีที่นิยมนำมาใช้ในการกระตุ้น ได้แก่ ซิงก์คลอไรด์ กรดฟอสฟอริก และโพแทสเซียมไฮดรอกไซด์ ถ่านกัมมันต์จากวัสดุเหลือใช้ทางการเกษตรที่ผลิตได้มีการนำไปใช้เป็นตัวดูดซับในกระบวนการดูดซับ ซึ่งเป็นการกำจัดสารมลพิษในน้ำที่ใช้งานอย่างแพร่หลาย และพบว่าถ่านกัมมันต์จากวัสดุเหลือใช้ทางการเกษตรสามารถกำจัดสารมลพิษต่างๆ ได้แก่ โลหะหนัก สีย้อม สารกลุ่มฟีนอล สารฆ่าแมลง และศัตรูพืชในน้ำได้อย่างมีประสิทธิภาพ คำสำคัญ: ถ่านกัมมนต์ วัสดุเหลือใช้ทางการเกษตร การกระตุ้น การกำจัดสารมลพิษ Abstract The article aimed to focus on the literature reviews, summaries and disseminations of knowledge about the preparation of activated carbon from agricultural residues by chemical activation for the application of pollutant removal in water. The high surface area and pore volume of activated carbon is 600 – 2,400 m2/g and 0.20 – 1.00 cm3/g, respectively. Their component is consisted of 80 – 90% of carbon. Agricultural residues, e.g., rice straw, corncob, coconut shell, coconut coirpith, palm shell, hardwood, can be used for the preparation of activated carbon. The preparation of activated carbon comprises two steps including the carbonization and activation. In addition, the activation step can be classified into two methods: physical and chemical activation. Chemical activation is, however, applied to prepare activated carbon more than physical activation due to lower temperature and less time consuming with high surface area and pore volume of activated carbon. The chemical agents, such as ZnCl2 H3PO4 and KOH are favorably used for the activation. Activated carbons from agricultural residues are applied as absorbent in the adsorption process and widely used for the pollutants removal in water. It is found that the efficiency of activated carbon from agricultural residues can be used to remove the pollutants, e.g., heavy metals, dyes, phenols and pesticides, in water. Keywords: Activated carbon, Agricultural residues, Activation, Pollutant removal